Railway Actuator Made of Magnetic Elastomers and Driven by a Magnetic Field - Umehara, Yasuhiro (Polymers (Basel), 2018)
We fabricated a mono-link using bimodal magnetic elastomers that demonstrate drastic changes in the elastic modulus by magnetic fields. The magnetic elastomer is bimodal consisting of large magnetic particles and nonmagnetic fine particles. The storage modulus for bimodal magnetic elastomers was altered from 2.2 × 10(5) to 1.7 × 10(6) Pa by a magnetic field of 500 mT. Compression tests up to a strain of 20% also revealed that the on-field stress for the bimodal magnetic elastomer was 1.24 times higher than the off-field stress. The bimodal magnetic elastomer was synthesized for the mono-link and was mounted on the bogie of a railway vehicle. A running test exhibited that the wheel lateral force was reduced by 20% by applying a magnetic field of 390 mT.